Cultivating Critical Thinking Strategies and Skills in English Education - Pandey, Shiv Ram (Journal of Janta Multiple Campus, 2025)
This article presents perspectives on cultivating critical thinking strategies and skills in English education. This is a review article where an in-depth information and insight have been reviewed. The techniques that are used in this study are document review and theoretical knowledge. Relevant literature is reviewed to make the study conceptually and theoretically reliable and authentic. The study reveals that critical thinking is thinking upon thinking. It does not take anything as for granted. It believes in questioning and open-mindedness. Thinking critically boosts creativity and enhances the way we use and manage time. Critical thinking not only describes the ability to think in accordance with the rules of logic and probability, but also the ability to apply these skills to real-life problems, which are not content-independent. Critical thinking provides with a more insightful understanding on oneself. It offers an opportunity to be objective, less emotional, and more open-minded as we appreciate others' views and opinions. By thinking ahead, we gain the confidence to present fresh perspectives and new insights.